Leader-member exchanges with leaders who have worked for 25 years in health institutions - Frøydis Vasset; Lisbeth Fagerstrøm; Marianne Frilund (Wiley, 2023)
Abstract Aim The aim is to investigate long‐term leader experiences with leader- member exchanges (LMX) over 25 years. Leader-member exchanges focus on relational power and communication exchanges between leaders and employees when they communicate with each other or perform an action. Design This qualitative study is characterized by a phenomenological hermeneutical design and is based on the informants' interpretation and construction of meaning. Method A qualitative study with eight interviews with supreme nurse leaders from the Norwegian and Finnish health care services. Result The data analysis and interpretation show that relationships are built through trust, dialogue and confirmation and are affected by other contextual aspects such as the organizational size or workload and human factors such as safety, angst, and self‐esteem. The informants fight for their subordinates. Interprofessional management and obtaining good relations with the doctors was challenging. No Patient or Public Contribution